The profile of science process skills of junior high school students in Lembata - V A Tonjo; T R Ramalis; Hernani Hernani (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This preliminary study aims to obtain data on the extent to which the science process skills (SPS) has been developed in the process of science learning in one of the private junior high school in Lembata, which later taken as a consideration for promoting a SPS-oriented learning. Data were collected through questionnaires filled out by students and interviews with science teachers. Based on the results of the analysis, it is known that science learning in schools has not been fully able to bring up the skills expected; for the average score of aspects of observing, designing and making, predicting, measuring and calculating, hypothesizing and communicating, only reached less than 65%. This low achievement is due to the applied methods, models and learning strategies, which tend to lead students having conceptual understanding, while the procedural, factual and other basic understanding of science are poorly trained. Based on this case, it is necessary to do further research in the form of application of a method and learning strategy that is able to enhance student's SPS.